Comprehensive analysis of transcriptome and microbiome in colorectal cancer with synchronous polyp patients - Wang, Yubin; Liu, Yongfeng; Liu, Xiaoqiang; Xu, Pengwei; Luo, Mingjie; Huang, Anle; Su, Zhijun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundColorectal cancer (CRC) is a prevalent and lethal malignancy, with the role of gut microbiota in its development still unclear. This study examines differences in gut microbiota between CRC patients and healthy controls and explores their association with host gene expression to identify potential diagnostic and therapeutic targets.MethodsFecal samples from 10 CRC patients and 13 healthy controls were subjected to 16S rRNA sequencing. Transcriptome sequencing of tumor tissues, normal mucosa, and colorectal polyps from same 10 CRC patients was performed to identify differentially expressed genes (DEGs). Pearson correlation analysis was employed to associate operational taxonomic units (OTUs) with host gene expression.Resultsβ-diversity analysis showed significant differences in microbiota between CRC patients and controls (P < 0.01). LEfSe identified 38 distinct bacterial taxa, with genera such as Bacteroides, Peptostreptococcus, and Parabacteroides being enriched in CRC patients. Transcriptome analysis uncovered 1,026 DEGs. Notably, TIMP1 and BCAT1 were positively correlated (r > 0.76, P < 0.01) with pathogenic bacteria like Fusobacterium nucleatum and Peptostreptococcus stomatis. Tumor-related genes TRPM4, MYBL2, and CDKN2A were significantly upregulated and correlated with specific bacterial taxa.ConclusionThis study underscores the significant alterations in gut microbiota associated with CRC and reveals novel correlations between specific microbes and host gene expression, offering potential diagnostic markers and therapeutic targets for CRC.